Proteome Analysis Based on Human Recombinant Antibody Microarrays - Ingvarsson, J. (Scand J Immunol, 2008)
Protein microarrays will play a key role in the postgenomic era and offer a unique possibility to perform high‐throughput global proteome analysis. A chip can be printed with thousands of protein probes (e.g. antibodies), the biological sample added (e.g. a proteome) and any binding detected. We aim to develop protein microarrays based on human recombinant scFv antibody fragments for global proteome analysis. The concept of comparing proteomic maps of healthy versus diseased samples will allow disease‐specific proteins to be detected. In fact, antibody microarrays will allow us to perform comparative proteome analysis on any sample format in a species‐independent manner, as long as a proteome can be isolated. However, the complexity of proteomes, containing several thousands of different proteins, is a problem. Here, we have designed antibody microarrays targeting the water‐soluble fraction of a proteome. To this end, an anticytokine antibody array was developed and human dendritic cells (±activation) was used as model system. The results showed that our antibody microarrays could be used to examine the cytokine profile in complex samples. Furthermore, we have taken the first steps towards comparing our results with those of other technologies on both the protein and gene level. Due to the complexity of the model proteome, we also examined the possibility to prefractionate the proteome in a simple one‐step procedure (based on size) prior to the labelling step. In more detail, the sample proteome was fractionated into two fractions using membrane devices with different molecular weight cut‐offs. The results showed that the fractionation considerably enhanced the assay sensitivity allowing cytokines in the pg/ml range to be readily detectable.